Evaluation of Deodorizing Effects of Saccharina japonica in 10-Month-Old ICR Mice Using a Novel Odor Marker Associated with Aging. (9th February 2022) - Kim, Ji Eun; Choi, Yun Ju; Lee, Su Jin; Gong, Jeong Eun; Seong, Ji Eun; Park, So Hae; Hwang, Dae Youn
Abstract : The potential deodorizing effects of Saccharina japonica have been evaluated by determining their deodorizing performance, but they are yet to be validated in experimental animals. The deodorizing effects of S. japonica were examined in an animal model using a novel odor marker associated with aging by comparing the concentration of odor component in urine obtained from two- and 10-month-old ICR mice using gas chromatography-mass spectrometry (GC-MS), and the changes in the trimethylamine (TMA) concentration, ammonia level, and structure of sweat gland were determined after exposing 10-month-old ICR mice to 70% ethanol extract of S. japonica (EESJ) for four weeks. In vitro analysis was performed to confirm the composition of EESJ with respect to the total flavonoid contents (TFC, 28.6 ± 2.5 mg/g), total polyphenol contents (TPC, 107.3 ± 8.9 mg/g), and total condensed tannin contents (TTC, 65.7 ± 5.2 mg/g) contents, as well as to the deodorizing performance to ammonia and acetic acid (91.2 ± 7.8% and 54.8 ± 6.3%, respectively). In vivo analysis revealed TMA to be the novel odor marker associated with aging among the 19 odor components evaluated, considering the higher concentration in the urine of 10-month-old ICR mice. The peak area of TMA on the gas chromatogram was significantly lower in the 10-month-old ICR mice treated with EESJ than in the two-month-old mice. A similar decrease was observed in the level of ammonia obtained from the dirty bedding of the EESJ-treated group. Moreover, tissues obtained from the mouse foot of the group exposed to EESJ showed a dose-dependent decrease in the gland tube number of sweat glands and the TMA dehydrogenase transcription level. Overall, these results provide novel evidence that the administration of EESJ helps reduce the body TMA and ammonia concentrations, resulting in reduced odor and a decrease in the number of sweat glands and the expression of TMA dehydrogenase in the ICR mouse feet.